The history of the special relationship : the relations between France and South Africa from 1958 to 1974 - (:unkn) unknown (My University, 2013)
Based on the original French and South African archives, this dissertation examines the relationship between France and South Africa under the administration of Charles de Gaulle et Georges Pomidou. Several elements explain why this relation may be qualified as « special »: the fact that South Africa didn’t belong to the traditional zone of French influence, the context in which this relation emerges (the process of decolonization along with the international condemnation of the regime of apartheid), its specialization (the close cooperation in the military and nuclear field) and its official atypical frame. Divided into four chronological parts, the dissertation presents the evolution of this « special relationship » and its different dimensions: bilateral (relations in military, nuclear and economic field), regional (relations in Southern Africa, in zone of the Indian Ocean and in Africa) and multilateral (debats at UN, IMF and EEC). By analyzing the discussions within the French institutions and the statements in international arena, this study reconstructs the ambiguous attitude of France towards the question of apartheid, the contradictions of the French policy of national independence as well of the French African policy. While the dissertation emphasizes the official framework, it also tempts to analyses the role of intermediates (parliamentarians, enterprises and military industry) in the conduct of French policy towards South Africa.
Keywords: African Research